The impact of video games on the speed of visual processing in individuals - Yeo, Hui Ting (2015)
Video games are being consumed by people of all ages and a significant amount of time and money are spent on these games. With the amount of resources involved in the video gaming industry, it is not surprising that the pros and cons of video game playing have been under scrutiny, especially its impact on impressionable children and adolescents. Hence, the purpose of our review paper is to look into the positive effects of video game engagement, specifically, the impact on the speed of visual processing in individuals. In our review, we begin by defining video games as well as the various types of video games currently available. Next, we look at speed of visual processing in terms of its measures, the factors that may affect it, as well as the implications of a superior speed of visual processing. We reviewed studies in the existing literature that have investigated the relationship between video game playing and speed of visual processing. It has been found that video game playing does have advantageous effects on the speed of visual processing. Lastly, we identified some limitations in the existing literature and suggested the direction future studies can take.